Reviewing Accountability and Transparency Practices of Campaign Fund Financial Reporting - Nita Nita; Febrian Kwarto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
This study reviews and assesses accountability practices in campaign fund financial reports. In addition, this study also aims to analyze the level of compliance of political parties and legislative candidates in the transparency of campaign fund disclosure according to the applicable reporting standards according to the general election commission. Research subjects include party members, candidates, accounting experts, and the public. Data were collected through surveys, interviews, and documentation, analyzed using qualitative methods. The findings reveal six themes indicating that political parties view accountability as a tool for performance measurement, financial balance verification, and evidence of compliance. Campaign fund management also acts as a communication bridge between candidates, parties, and stakeholders, fulfilling accountability responsibilities to the government, which provides KPU-permitted contributions. Additionally, transparency in campaign fund reporting reflects compliance with election commission standards, which influences the commission's assessment of candidates' responsibilities, ensuring campaign funds are reported separately and accurately per regulatory requirements.